Ron Arad no discipline - Arad, Ron 1951; Antonelli,Paola; Hall, Emily; O'Brien Beth; Amsterdam (Netherlands). Stedelijk Museum; Centre Georges Pompidou; Museum of Modern Art (New York, N.Y.). (New York Museum of Modern Art Distributed by D.A.P., 2009)
"Published to accompany the first major retrospective of Arad's work in the U.S., this volume features an interview with the artist and essays on his use of innovative materials and technology, his role as an educator and communicator on the importance of design and his place in the world of design and the larger art market. A lavishly illustrated plate section provides visual and written documentation of approximately 80 works"--Provided by publisher.
"I want to make new things" : innovation in the work of Ron Arad Ingeborg de Roode -- Rod Arad in conversation with Marie-Laure Jousset -- No discipline : Rod Arad at the Royal College of Art Paola Antonelli -- You look up escape artist Jonathan Safran Foer.
Includes bibliographical references (page 210) and index.
FA-2740g donated by Franklin Bobadilla.
Keywords: Arad, Ron -- 1951- -- Exhibitions; Furniture design -- History -- 21st century -- Exhibitions; Design -- History -- 21st century -- Exhibitions; Design and technology -- Exhibitions